Adapting the WHO Age-Friendly Cities Framework to Address Challenges in Kenya’s Urban Informal Settlements - Fidella (Magyar Gerontológia, 2025)
Kenya’s rapidly growing and ageing population, and the urbanization presents urgent challenges and opportunities for creating urban environments that truly support older adults.